THE IMPROVEMENT OF GROUPING SKILLS AND CONCEPT’S MASTERY WITH LEARNING CYCLE 3E - tarik azis; nina kadaritna; tasviri efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2013)
Learning effectiveness is a measure related to the level of success of a learning process. Said effective learning and by contributing to student learning outcomes if the student learning outcomes showed statistically significant differences between the early understanding of the development of understanding after this learning. The research done to describe the effectiveness of LC 3E model in improving grouping skills and concept’ mastery. LC 3E model consists of 3 phases which exploration, explaination, and elaboration. Samples were students of Senior High School State 1 Pekalongan XI Sains 1 and XI Sains 4 class in odd semester of School Year 2012-2013 that have similar characteristics. This study uses a quasi-experimental method with Non Equivalent Control Group Design.  Effectiveness of the LC 3E model was measured by an increase in N-significant gain. The results showed that the mean n-Gain of grouping skill control and experiment classes respectively 0.49 and 0.66, and the mean n-Gain concept’s mastery for grade control experiments respectively 0.53 and 0, 65.  Based on the research results, it was concluded that the learning cycle instructional model 3E effective in improving grouping skills and concept’s mastery.Keywords: Learning Cycle three phase model, grouping skill, and concept’s mstery